Does cognition influence the functional impairment degree of post-stroke patients? - Silva, Ozair Argentille Pereira da; Cirne, Gabriele Natane de Medeiros; Filho, Edson Meneses da Silva; Cacho, Enio Walker Azevedo; Cacho, Roberta de Oliveira (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: The post-stroke subjects have several sequelae after the disease, which should be investigated and identified so that the clinical treatment includes these people in all aspects. Objective: To identify if there is a correlation between level of education, cognitive function, functional independence and the sensory-motor abilities of post-stroke subjects. Methods: The sample consisted of 27 post-stroke patients who were evaluated through the following scales: Mini-Mental State Exam (MMSE), Functional Independence Measure (FIM) and Fugl-Meyer Assessment (FMAA) and sociodemographic data collection. Results: A positive and statistically significant correlation was found between MMSE and FIM. When the scores were correlated with education, motor FIM (p = 0.005), total FIM (p = 0.006), temporal orientation MMSE (p = 0.03) and total MMSE (p = 0.01) were statistically significant. Furthermore, a positive correlation but not statistically significant was identified between the cognitive levels and sensory-motor impairment assessed by FMAA. Conclusion: It is concluded that the education of subjects is associated with motor function after stroke. In addition, cognitive impairments interfere with the level of post-stroke functionality, but do not have a direct influence on the degree of sensory-motor impairment.